Longwall top coal caving automation concept - Nikitenko Sergey; Kiessling Ulf; Kizilov Sergey; Nikitenko Mikhail (E3S Web of Conferences, 2021)
This paper describes history of the longwall top coal caving technology. The devices capable to promote wider application of LTCC are discussed. The advantages, shortcomings and their elimination methods are specified. The authors designate the objectives to be met to implement the maximum potential of LTCC. The industry approach to these objectives is exemplified. The applicability of LTCC in combination with new-generation powered roof support with coal outlet in supported area in longwalls is discussed. The ways of finding solutions to the set problems are proposed.